1991
DOI: 10.1002/ajmg.1320380243
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome in an extended family with special reference to an affected male with Klinefelter Syndrome

Abstract: We report on a large family (4 generations), with 77 studied individuals, 9 mentally retarded males, and one affected female with fragile X syndrome [fra(X)]. The analysis of 6 flanking polymorphic DNA markers showed that the affection is transmitted, through the carrier daughters to the grandsons and the greatgrandsons and that the great-grandfather is a transmitting male. This observation led us to question the importance of these clinically normal males, who are nonexpressing carriers and termed transmittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Parental origin studies have been reported in six of the previous cases [Filippi et al, 1988;Kupke et al, 1991;Schnur et al, 1986;Voeckel et al, 1991], and only one of those showed paternal nondisjunction [Schnur et al, 1986]. Our case adds to the presumption that the combination of Klinefelter syndrome and fragile X syndrome is not a result of the maternal carrier state predisposing to nondisjunction but pure coincidence.…”
Section: To the Editorsupporting
confidence: 53%
See 1 more Smart Citation
“…Parental origin studies have been reported in six of the previous cases [Filippi et al, 1988;Kupke et al, 1991;Schnur et al, 1986;Voeckel et al, 1991], and only one of those showed paternal nondisjunction [Schnur et al, 1986]. Our case adds to the presumption that the combination of Klinefelter syndrome and fragile X syndrome is not a result of the maternal carrier state predisposing to nondisjunction but pure coincidence.…”
Section: To the Editorsupporting
confidence: 53%
“…So far at least 14 cases with 47,XY,fra(X) have been reported [Filippi et al, 1988;Froster-Iskenius et al, 1982;Fryns et al, 1983Fryns et al, , 1988Kleczkowska et al, 1988;Kupke et al, 1991;Mavrou et al, 1988;Pueschel et al, 1987;Voeckel et al, 1991]. Parental origin studies have been reported in six of the previous cases [Filippi et al, 1988;Kupke et al, 1991;Schnur et al, 1986;Voeckel et al, 1991], and only one of those showed paternal nondisjunction [Schnur et al, 1986].…”
Section: To the Editormentioning
confidence: 99%
“…:, t. "': 132 133 The combined results of studies from England, the United States, Australia, and The Netherlands (table 3), irrespective of methodological differences, showed, in a total of 4670 mentally retarded subjects, 30 (0.6%) newly diagnosed fragile X patients.38 133 138 In the general population, a premutation carrier frequency among females of ±1/250 has been observed. '38 1 4 This reflects the proportional excess of relatively stable premutation sized alleles over full mutation alleles.…”
Section: Fmrp Antibody Testmentioning
confidence: 98%